Phenotypic spectrum associated with de novo mutations in QRICH1 gene. Issue 2 (21st December 2017) - Ververi, A.; Splitt, M.; Dean, J. C. S.; ,; Brady, A. F.
Abstract : Rare de novo mutations represent a significant cause of idiopathic developmental delay (DD). The use of next‐generation sequencing (NGS) has boosted the identification of de novo mutations in an increasing number of novel genes. Here we present 3 unrelated children with de novo loss‐of‐function (LoF) mutations in QRICH1, diagnosed through trio‐based exome sequencing. QRICH1 encodes the glutamine‐rich protein 1, which contains 1 caspase activation recruitment domain and is likely to be involved in apoptosis and inflammation. All 3 children had speech delay, learning difficulties, a prominent nose and a thin upper lip. In addition, 2 of them had mildly raised creatine kinase (CK) and 1 of them had autism. Despite their small number, the patients had a relatively consistent pattern of clinical features suggesting the presence of a QRICH1 ‐associated phenotype. LoF mutations in QRICH1 are suggested as a novel cause of DD. Abstract :